Genotype Phenomenon and Marriage Compatibility among Nigeria Pentecostals: An Ethical Response of Mountain of Fire and Miracles Ministries - Gbenle, Grace Olayinka (NIU Journal of Social Sciences, 2018)
The issue of blood group and genotype compatibility has received various attentions of scholars in different fields of endeavour. Many Christians believe in the power of God to change blood group with the confession of the biblical statement that with God nothing is impossible (Luke 1:37). By this belief, many Christians have made choices in the area of marriage especially with regard to blood and genotype compatibility in a bid to putting God to test. However, this paper focuses on the ethical response of Mountain of Fire and Miracles Ministries to the issue of genotype as an essential aspect of marriage. The Church is now trying to re-orientate people on the need for checking on the compatibility of spouses before marriage. The issue of genotype compatibility is discussed under the ambit of utilitarian theory of ethics. This theory postulates that a right action is the one that produces much pleasure and less pain for those who are affected by such action. It places values on an action benefitting majority of population affected by the action than the pain that could be associated with that action. The research also seeks to use the observation and focus group discussion method in carrying this research as this provides a wide range of information on subject matter. The response of the Church to genotype compatibility of spouse and their intervention by means of carrying out the medical examination by themselves have also helped in sensitizing the members on the essence of checking their compatibility in order to reduce the number of children born with ‘SS’ genotypes and also reduce other social and economic problems tied to taking wrong genotype and blood compatibility in marriage. Keywords: Genotype, marriage compatibility, Nigerian Pentecostals, Ethics, Mountain of Fire and Miracles Ministries